Successful Use of Two Thrombolytic Drugs in Prosthetic Mitral and Aortic Valve Thrombosis - Shayesteh Gheibi; Aliasghar Farsavian; Maryam Nabati; Gohar Eslami (Mazandaran University of Medical Sciences, 2019)
Introduction: Prosthetic valve thrombosis is a rare and severe complication of valve replacement, most often encountered with a mechanical prosthesis. The significant morbidity and mortality associated with this condition warrant rapid diagnostic evaluation. Although surgery is the first-line therapy in symptomatic obstructive mechanical valve thrombosis, thrombolytic therapy has been used as an alternative.  Case Description: In this case report, we describe a 46-year-old man with a history of the mitral valve and aortic valve replacement 2 years ago. In echocardiography, we detected a mobile mass on the atrial side of the mitral valve prosthesis and a fixed one on the leaflet of the mechanical aortic valve with a high gradient. To save his life, we used double thrombolytic therapy considering the patient's hemodynamic situation and the risk of bleeding. Although a routine dose of reteplase and streptokinase was considered, we administered these two thrombolytic drugs together within 72 hours.  Conclucsion: Ultimately we succeeded with this method without any significant or life-threatening adverse effects, and the patient was discharged after an optimal anticoagulation therapy.